A decade of research contributions and emerging trends in the International Journal of STEM Education - Thomas K. F. Chiu; Yeping Li; Meixia Ding; Jonas Hallström; Milo D. Koretsky (International Journal of STEM Education)
Abstract In this editorial, we review 400 articles and reviews published in the International Journal of STEM Education during its first decade (2014–2023). Using bibliometric analysis, we examine these publications to assess the journal’s major contributions to STEM education research and identify emerging trends over the years. The results present a dynamic picture of the growth of STEM education, highlighting key topics, such as STEM integration, equity, and emerging technologies. These findings also reveal evolving “hot topics” that reflect the shifting interests of researchers in the field. This review suggests that many areas of STEM education research are still in the growth phase. We encourage readers to use these insights as a foundation for developing future research agendas and advancing STEM education globally.